2012
DOI: 10.4101/jvwr.v5i1.6173
|View full text |Cite
|
Sign up to set email alerts
|

How do People with Disability Use and Experience Virtual Worlds and ICT: A Literature Review

Abstract: There is wide agreement that information and communication technology (ICT) is a valuable tool for people with disability. Several research disciplines have focused on how people with disability can take advantage of the technology available for social, educational and personal purposes. Virtual worlds represent the latest addition to the technologies available, yet there is little research on how people with disability use and experience virtual worlds. A review of research conducted in different disciplines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 67 publications
2
45
0
1
Order By: Relevance
“…However, we aimed to identify usage and preferences in patients who have access to ICT and having an email address suggests the latter. Future studies should also include patients in rehabilitation with low level of access to ICT [10], lack of ICT experience [10,22,37] and personal traits for ICT utilization (e.g., age and health condition) [38] in order to better understand how to enable all patients to benefit from of e-health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we aimed to identify usage and preferences in patients who have access to ICT and having an email address suggests the latter. Future studies should also include patients in rehabilitation with low level of access to ICT [10], lack of ICT experience [10,22,37] and personal traits for ICT utilization (e.g., age and health condition) [38] in order to better understand how to enable all patients to benefit from of e-health.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, long-term medical care needs could be addressed at significant lower expenditures [5], by means of improved accessibility to rehabilitation programs for clients with mobility impairments [6][7][8], expanded continuity of care and increased self-management by promoting personalized care, choice and personal autonomy [9]. Indeed, a number of studies showed that e-health is acceptable for subgroup of patients in rehabilitation care [9][10][11] and has the potential to support management of chronic conditions such as Alzheimer's/ dementia [12], diabetes [13,14] and COPD [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the existing literature regarding the use of virtual environments for individuals with disabilities is somewhat limited, some researchers are beginning to recognise its utility for this sample of individuals (Stendal, 2012). Further, the clinical applications of virtual reality systems, more generally, are apparent in various research agendas (Reid, 2002;Rizzo et al, 2002).…”
Section: Resultsmentioning
confidence: 95%
“…This assertion is highlighted in a recent review by Stendal (2012), who notes the lack of research into the ''social aspects, work opportunities and personal value of virtual worlds'' (p. 1) for individuals with disabilities. With relatively limited leisure opportunities, these individuals are proposed to be at risk of developing a range of negative psychological symptoms, such as dependant behavioural patterns, learned helplessness and depression (Turner & Beiser, 1990;Turner & Noh, 1988).…”
Section: Virtual Environments and Individuals With Physical Disabilitiesmentioning
confidence: 87%
“…Although the internet is now firmly entrenched in mainstream society, access to the internet has highlighted the inequalities which exist for some groups, and people with intellectual disability in particular (Chadwick et al, 2013;Stendal, 2012). Not only does the internet enable people with intellectual disability to express their sexuality to engage in meaningful relationships, but all types of associations, as not all contact need necessarily be sexually based.…”
Section: Introductionmentioning
confidence: 99%